The structure of an integrin/talin complex reveals the basis of inside-out signal transduction. - Anthis, N; Wegener, K; Ye, F; Kim, C; Goult, B; Lowe, E; Vakonakis, I; Bate, N; Critchley, DR; Ginsberg, M; Campbell, I (2009)
Fundamental to cell adhesion and migration, integrins are large heterodimeric membrane proteins that uniquely mediate inside-out signal transduction, whereby adhesion to the extracellular matrix is activated from within the cell by direct binding of talin to the cytoplasmic tail of the beta integrin subunit. Here, we report the first structure of talin bound to an authentic full-length beta integrin tail. Using biophysical and whole cell measurements, we show that a specific ionic interaction between the talin F3 domain and the membrane-proximal helix of the beta tail disrupts an integrin alpha/beta salt bridge that helps maintain the integrin inactive state. Second, we identify a positively charged surface on the talin F2 domain that precisely orients talin to disrupt the heterodimeric integrin transmembrane (TM) complex. These results show key structural features that explain the ability of talin to mediate inside-out TM signalling.